Legal Analysis of Iron Sand Mining Conflict in Kulon Progo Regency, Yogyakarta - Shabarudin Shabarudin; Diding Rahmat (UNIFIKASI : Jurnal Ilmu Hukum, 2022)
The facts on the ground show that most mining in Indonesia is carried out using an open pit mining so that it has an impact on environmental damage. This study aims to determine the factors that cause iron sand mining conflicts and develop a concept of iron sand mining conflict resolution in Kulonprogo Regency, Yogyakarta Special Region Province. The research method used is juridical-empirical law research, with a juridical and case approach, which is then analyzed qualitatively. The results in this study are broadly classified as mining conflicts that occurred in Kulon Progo Regency, Yogyakarta Special Region, which can be divided into two, namely nuanced or legal conflicts (legal conflicts) and social conflicts (social conflicts). Then, the conflict resolution was carried out and targeted two things, namely the harmonization of laws and regulations that were related and used directly in the context of iron sand mining in the area. As well as policy making by involving all stake holders (related parties).